Audience Perception of Radio Coverage of Lassa Fever in Adamawa and Taraba State, Nigeria - Bonzena, John Rejoice; Lucas, Joseph M. (Lembaga Yasin AlSys, 2024)
This study examined audience perceptions of radio coverage of Lassa fever in Adamawa and Taraba States, focusing on Adamawa Broadcasting Corporation (ABC) radio and Taraba State Broadcasting Services (TSBS) radio. The study was anchored in the Agenda-Setting Theory and employed a descriptive survey approach. A valid sample of 327 respondents was used to collect quantitative data via a questionnaire, which were analyzed using descriptive statistical tools. The findings revealed that, despite the widespread availability of radio stations, listeners in Yola and Jalingo had limited exposure to programs addressing Lassa fever. The study further found that the audience generally perceived radio messages on Lassa fever as informative; however, there was a preval_ent reluctance among radio listeners to adopt the recommended preventive measures against Lassa fever as advocated in the radio programs. The study also identified various challenges encountered by the audience, including disinterest in campaign messages, language barriers, technical complexity of the content, inappropriate timing of broadcasts, and socioeconomic constraints. Based on these findings, the study recommends that radio stations dedicate more programs and time to creating awareness about Lassa fever, make content more engaging and interactive, address language barriers, optimize the timing of broadcasts, consider socioeconomic constraints, and leverage multi-channel communication approaches.